Effects of Narrative Exposure Therapy on Posttraumatic Stress Disorder, Depression, and Insomnia in Traumatized North Korean Refugee Youth. Issue 3 (26th March 2020) - Park, Jinme K.; Park, Jinah; Elbert, Thomas; Kim, Seog Ju
Abstract: Refugees affected by multiple traumatic stressors are at high risk for developing trauma‐related mental disorders, including posttraumatic stress disorder (PTSD), depression, and insomnia, which is sometimes overlooked. The present study examined the effectiveness of narrative exposure therapy (NET) on trauma‐related symptoms in a sample of North Korean refugee youth. We focused on sleep patterns in addition to changes in symptom severity for PTSD, depression, and internalizing and externalizing symptoms. North Korean refugee youth ( N = 20) with PTSD were assigned to either an NET‐based treatment group or a control group, which consisted of treatment as usual (TAU). There were clinically significant reductions in PTSD, depression, and internalizing and externalizing symptoms for the NET group, Hedges' g = 3.6, but not the TAU group. The change in diagnostic status for PTSD was more notable for participants in the NET group compared to the TAU group. Of note, NET also produced a significant improvement in insomnia symptoms and sleep quality, Hedges' g = 2.1. The substantial recovery regarding overall posttraumatic symptoms in the NET group was observed 2 weeks after the end of treatment and remained stable at 6‐month follow‐up. The results of the present study suggest that NET may be a treatment option for traumatized North Korean refugee youth and may also be effective for the treatment of sleep problems that arise from traumatic experiences. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Efectos de la Terapia de Exposición Narrativa sobre TEPT, Depresión e Insomnio: Un estudio con jóvenes refugiados traumatizados norcoreanos EXPOSICIÓN NARRATIVA, TEPT, DEPRESIÓN E INSOMNIO Los refugiados afectados por múltiples estresores traumáticos están en alto riesgo de desarrollar trastornos mentales relacionados al trauma, incluyendo el trastorno de estrés postraumático (TEPT), depresión e insomnio, el cual es a veces pasado por alto. El presente estudio examinó la efectividad de la Terapia de Exposición Narrativa (NET en su sigla en inglés), sobre los síntomas relacionados al trauma en una muestra de jóvenes refugiados norcoreanos. Nos enfocamos en los patrones de sueño además de cambios en la severidad de síntomas para TEPT, depresión y síntomas internalizantes y externalizantes. Los jóvenes refugiados norcoreanos ( N = 20) con TEPT fueron asignados a un grupo de tratamiento basado en NET o a un grupo control que consistía en tratamiento habitual (TAU en su sigla en inglés). Hubo reducciones clínicamente significativas en TEPT, depresión y síntomas internalizantes y externalizantes para el grupo NET, g de Hedges g = 3.6, pero no en el grupo TAU. El cambio en el estado diagnóstico para TEPT fue más notable en los participantes del grupo NET comparado con el grupo TAU. Es de notar que NET también produjo una mejoría significativa en los síntomas de insomnio y calidad del sueño, g de Hedges g = 2.1. La recuperación substancial en relación a los síntomas postraumáticos en conjunto, en el grupo NET se observó 2 semanas luego del término del tratamiento y permaneció estable en el seguimiento a los 6 meses. Los resultados del presente estudio sugieren que la NET podría ser una opción de tratamiento para los jóvenes refugiados norcoreanos traumatizados y puede ser también efectiva para el tratamiento de problemas del sueño que surgen de experiencias traumáticas. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Effects of Narrative Exposure Therapy on PTSD, depression, and insomnia: A study with traumatized North Korean refugee youth Traditional Chinese 標題: 敘事暴露治療對PTSD、抑鬱症與失眠的療效:針對受創的北韓青少年難民的研究 撮要: 承受多個創傷壓力源影響的難民, 有高風險發展出創傷相關的精神疾病, 包括創傷後壓力症(PTSD)、抑鬱症與失眠, 但這風險時被忽視。本研究透過北韓青少年難民樣本, 檢視敘事暴露治療(NET)對創傷相關症狀的療效。除了檢視PTSD、抑鬱症、內化與外化症狀的嚴重度改變外, 我們更專注檢視睡眠模式。患PTSD的北韓青少年難民樣本(N = 20), 獲分配到NET為本的治療組或對照組, 後者提供平常的治療(TAU)。NET組別的樣本其PTSD、抑鬱症、內化與外化症狀都有臨床顯著的改善 (Hedges' g = 3.6), 而TAU組別則沒有。兩組相比, NET組的樣本其PTSD診斷的改變較為明顯。值得留意的是, NET亦顯著改善了樣本的失眠症狀和睡眠質素 (Hedges' g = 2.1) 。NET組別的樣本, 其整體創傷後症狀有顯著改善。我們於樣本完成療程兩星期後再次檢視療效;六個月後跟進時, 發現療效仍維持穩定。本研究的結果反映, NET對受創的北韓青少年難民來說, 可能是個治療方案, 而且可能可有效治療因創傷經歷引致的睡眠問題。 Simplified Chinese 标题: 叙事暴露治疗对PTSD、抑郁症与失眠的疗效:针对受创的北韩青少年难民的研究 撮要: 承受多个创伤压力源影响的难民, 有高风险发展出创伤相关的精神疾病, 包括创伤后压力症(PTSD)、抑郁症与失眠, 但这风险时被忽视。本研究透过北韩青少年难民样本, 检视叙事暴露治疗(NET)对创伤相关症状的疗效。除了检视PTSD、抑郁症、内化与外化症状的严重度改变外, 我们更专注检视睡眠模式。患PTSD的北韩青少年难民样本(N = 20), 获分配到NET为本的治疗组或对照组, 后者提供平常的治疗(TAU)。NET组别的样本其PTSD、抑郁症、内化与外化症状都有临床显著的改善 (Hedges' g = 3.6), 而TAU组别则没有。两组相比, NET组的样本其PTSD诊断的改变较为明显。值得留意的是, NET亦显著改善了样本的失眠症状和睡眠质素 (Hedges' g = 2.1) 。NET组别的样本, 其整体创伤后症状有显著改善。我们于样本完成疗程两星期后再次检视疗效;六个月后跟进时, 发现疗效仍维持稳定。本研究的结果反映, NET对受创的北韩青少年难民来说, 可能是个治疗方案, 而且可能可有效治疗因创伤经历引致的睡眠问题。